ACCELEROMETRY UNDERESTIMATES ENERGY EXPENDITURE IN CIRCUIT-BASED RESISTANCE TRAINING - Peinado,Ana Belén (2020)
ABSTRACT Introduction: Accelerometry is a very accurate method for determining energy expenditure (EE) in endurance training. However, further studies are needed to prove its accuracy in resistance training. Objective: To compare the EE obtained by accelerometry and indirect calorimetry in three different circuit resistance training circuits. Methods: Six overweight volunteers performed three sets in three resistance training circuits: machine circuit (MC), free-weight circuit (FWC) and resistance + aerobic circuit (RAC). EE was measured by indirect calorimetry using an Oxycon Mobile® and by the accelerometers SenseWear® Armband Pro2 and ActiTrainer®. Results: ActiTrainer® and SenseWear® underestimated EE in all circuits when compared to indirect calorimetry (p<0.05). The difference was greater in the FWC: 44.4% METs and 81.4% Kcal for ActiTrainer® and 32.3% METs and 24.9% Kcal for SenseWear® compared to indirect calorimetry. Conclusion: Both ActiTrainer® and SenseWear® underestimated EE when compared to indirect calorimetry in three different resistance training circuits. Level of evidence II; Diagnostic studies - Investigating a diagnostic test.